HISTORIOGRAFI AKUNTANSI INDONESIA MASA MATARAM KUNO (ABAD VII-XI MASEHI) - Novrida Qudsi Lutfillah; Eko Ganis Sukoharsono (Jurnal Akuntansi Multiparadigma, 2013)
Abstract. Historiography of Indonesian Accounting in The Ancient Mataram Kingdom Era (VII-XI Century). Historiography or historical writing in the history of scienceis the culmination of the entire history of the research activities. Historiography accounting in Indonesia can be seen in the study of accounting history of the Singosari Kingdom (1222-1292) and the study of accounting history during the reign of King Udayana, Bali (989-1011). This study used social archeology method as an analytical tool to explore the accounting historiography in the Ancient Mataram Kingdom (8-11 centuryAD), focusing on Taxation Accounting. Recording and reporting activities of taxation as the royal income indicates that the activity occurs contains the value of “Sepi ing Pamrih, Rame ing Gawe". Abstrak: Historiografi Akuntansi Indonesia pada Masa Mataram Kuno (Abad VII-XI Masehi). Historiografi atau penulisan sejarah dalam ilmu sejarah merupakan titik puncak seluruh kegiatan penelitian sejarah. Historiografi akuntansi di Indonesia dapat dilihat pada penelitian tentang sejarah akuntansi masa kejayaan Kerajaan Singosari (1222-1292) dan penelitian sejarah akuntansi pada masa pemerintahan Raja Udayana Bali (989-1011 Masehi). Penelitian ini menggunakan metode sosial arkeologi sebagai alat analisis dalam mengeksplorasi historiografi akuntansi di Jawa masa Kerajaan Mataram Kuno (abad 8-11 Masehi), dengan fokus pada Akuntansi Perpajakan. Pencatatan dan pelaporan aktivitas perpajakan sebagai pendapatan kerajaan mengindikasikan bahwa aktivitas yang terjadi mengandung nilai Sepi ing Pamrih, Rame ing Gawe.